Information Management and Exponencial Learning in Society 5.0: Foundations For an Integrated System - Oliveira, Dalbert Marques; Pereira, Patrícia Miranda (Bobcatsss, 2023)
Individuals use information to reduce discomfort, effort and errors. Thinking about it, headphones were invented, so that the music could be heard without disturbing others; household appliances, to reduce the effort in washing dishes or clothes; and calculating machines, so that human distraction would not cause an accident in calculating the weight that a bridge could bear. But the information has hardly changed the certainties and doubts about which is the most suitable college course to attend; what are the best practices that could contribute to the individual's daily life, during the academic career, which includes when and what to study, what to eat and what to do in their free time. It is undeniable that there is greater access to information, but many times, instead of browsing this information, the individual sinks into it. In addition, teachers and students remain stuck in curriculum, with the same menu being provided for carnivores, vegetarians or lactose intolerants. If before students were beaten with rules in their hands and were attacked psychologically, having to learn the same as everyone else, nowadays only rules have ceased to exist, at least in theory. Reducing errors in choosing a higher education course and the entire life that governs the academic path can be a dream for many individuals and an integrative system that collects information about the individual and guides him in his academic path could be an extremely useful compass. Know which college course to take; knowing which discipline, among the electives, to choose; know the right time to get up and sleep; what to do throughout the day; what and when to eat; they are all informational outputs that the utopian system could provide, in order to contribute to the individual's success. This paper will attempt to discuss these issues, investigating part of the enabling technologies in today's Society 5.0. The objective is to initiate a debate on the delegation to an integrative system of data, information and knowledge management, the success of individuals and society.